Fully Transradial Versus Transfemoral Approach for Percutaneous Intervention of Coronary Chronic Total Occlusions Applying the Hybrid Algorithm: Insights From RECHARGE Registry. (September 2017) - Bakker, Erik Jan; Maeremans, Joren; Zivelonghi, Carlo; Faurie, Benjamin; Avran, Alexandre; Walsh, Simon; Spratt, James C.; Knaapen, Paul; Hanratty, Colm G.; Bressollette, Erwan; Kayaert, Peter; Bagnall, Alan J.; et al.
Abstract : Background—: Small observational studies demonstrate the feasibility of transradial approach for chronic total occlusion (CTO) percutaneous coronary intervention. The aim of the current study is to assess technical success, complication rates, and procedural efficiency in fully transradial approach (fTRA) and transfemoral approach (TFA) in a large prospective European registry adopting the hybrid algorithm for CTO percutaneous coronary intervention (Registry of CrossBoss and Hybrid Procedures in France, the Netherlands, Belgium and United Kingdom, RECHARGE registry). Methods and Results—: We analyzed 1253 CTO percutaneous coronary intervention procedures performed according to the hybrid protocol in 17 European centers, comparing fTRA (single or biradial access) and TFA (single or bifemoral or combined radial and femoral access). fTRA was applied in 306 (24%) and TFA in 947 (76%) cases. The average Japanese CTO score was 2.1±1.2 in fTRA and 2.3±1.1 in TFA ( P =0.06). Technical success was achieved in 85% in fTRA and 86% in TFA ( P =0.51). Technical success was comparable for fTRA and TFA in different Japanese CTO score subgroups after multivariable analysis and after propensity adjustment. In-hospital major adverse cardiac and cerebral events occurred in 2.0% in fTRA and 2.9% in TFA ( P =0.40). Major access site bleeding occurred in 0.3% in fTRA and 0.5% in TFA ( P =0.66). fTRA compared with TFA had similar procedural duration (80 minutes [54–120 minutes] versus 90 minutes [60–121 minutes]; P =0.07), similar radiation dose (dose area product 89 Gray×cm 2 [52–163 Gray×cm 2 ] versus 101 Gray×cm 2 [59–171 Gray×cm 2 ]; P =0.06), and lower contrast agent use (200 mL [150–310 mL] versus 250 mL [200–350 mL]; P <0.01). Conclusions—: fTRA CTO percutaneous coronary intervention is a valid alternative to TFA with a high rate of success, low complication rates, and no decrease in procedural efficiency. Abstract : Supplemental Digital Content is available in the text.